The Influence of Gadget Usage on Learning Motivation Among High School Students at SMA Negeri 5 Kepulauan Tanimbar in Adaut Village, Selaru District - Lorulung, Dolly; Wairisal, Paulus Liberthy; Ubra, Franklin W (JENDELA PENGETAHUAN, 2025)
This study aims to analyze the effect of gadget usage on students' learning motivation at SMA Negeri 5 Kepulauan Tanimbar. A quantitative research method with a correlational approach was used to assess the strength of the relationship between gadget usage and learning motivation. The sample consisted of 85 students from grade X, selected using a census sampling technique. Data were collected through questionnaires, observation sheets, and a learning motivation test. The results of the analysis indicate that gadget usage significantly affects students' learning motivation. The regression coefficient value of 0.198 shows that gadget usage positively influences students' learning motivation. Both validity and reliability tests confirm that the instruments used in this study are consistent and valid. Therefore, the study concludes that wise and directed use of gadgets can improve students' motivation to learn. These findings underscore the importance of the role of teachers and parents in guiding students toward productive gadget use